Konsep Negara dalam Pemikiran Politik Ibnu Khaldun - Nizar, Samsul (Jurnal Demokrasi, 2003)
This article discusses about concept and urgency of state for human life, and characteristics of head of state based on political thinking of Ibnu Chaldun. It is indicated that political thinking of Ibnu Chaldun intended to build religious state based on Islam doctrine for human good. He suggested to understand the head of the state and its election need considering, social background, aspiration of the people in the state. To build the state all people need thinking and acting based on logical and realistical religious, avoiding emotional and egocentrical ways. Â  Kata Kunci: State, Khaldumâ€™s Political/philoshophy